Identification of West Siberian Quedius (Coleoptera, Staphylinidae) by COI barcodes calls for integrative taxonomy and curation of public DNA libraries - Valeria Krivosheeva; Maria Salnitska; Darya Semerikova; Angesom Abraham Gebremeskel; Anastasiya Ivanova; Alexey Solodovnikov (Deutsche Entomologische Zeitschrift, 2025)
Using West Siberian Quedius, we tested a widespread claim that DNA barcoding facilitates and accelerates taxonomic identification of arthropods. Our results indicate that even though neither BOLD nor GenBank had any barcodes from specimens of Quedius collected in West Siberia, these libraries were useful for the identification of our newly barcoded specimens from that region. However, correct identification was possible only after critical reciprocal evaluation of multiple conflicting data sources. Only six of 11–13 putative species could be confidently and easily identified to species level using the BOLD ID Engine or GenBank BLAST alone; all other cases required additional examination. Nevertheless, barcoding helped identify female singletons or teneral individuals that could not be identified morphologically and revealed that our own morphology-based species identification is prone to errors. Very subtle morphological differences between species may be revealed by DNA barcoding (e.g., Q. boops, Q. boopoides), and dubious morphology-based species concepts can be tested and potentially improved (e.g., specific limits of Q. molochinus, Q. fellmani, and Q. nitipennis). Finally, the use of barcoding helped record Q. balticus and Q. pseudolimbatus in West Siberia for the first time. The benefits of barcoding are valid only when reference barcodes in public libraries are correctly identified and kept up to date with changing taxonomy. We argue that more extensive use of barcoding in revisionary taxonomy will lead to faster-growing and better-curated DNA barcode libraries.